Mismatch Between Education and the Job Market: Challenges and Opportunities for Islamic Boarding Schools in Preparing Competitive Graduates in the Demographic Bonus Era - Kholilur Rahman,; Mamluatul Hasanah; Lala Olivia; Noer Halimah Asyihabi; Sofiyatin Rizkiyah (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2026)
In the era of the demographic bonus, the mismatch between education and labor market demands poses a significant challenge for pesantren, particularly as they educate a large population of youth entering the productive age group. This study aims to analyze the forms of mismatch occurring within pesantren, the contributing factors, and the strategic opportunities available to enhance graduates’ competitiveness. Employing a library research method, this study reviews literature on education–labor market mismatch, the transformation of pesantren education, and demographic dynamics in Indonesia. The findings indicate that pesantren continue to face mismatch due to structural constraints—such as weak curriculum alignment with national standards—and instrumental limitations including inadequate modern facilities and insufficient development of digital and vocational skills. Nevertheless, pesantren possess strategic assets through internal entrepreneurial units and extensive alumni networks that can facilitate industry partnerships and broaden employment opportunities. These findings highlight the potential of pesantren to play a pivotal role in reducing education–labor market mismatch and contributing to the optimal utilization of Indonesia’s demographic bonus.